Crédito hipotecário no Brasil: uma análise comparativa entre as praças de Belém e São Paulo (1870 – 1930) - LEANDRO, Leonardo Milanez de Lima (Universidade Federal do Pará, 2017)
The rubber extraction and coffee, in the final of the nineteenth and early twentieth century, formed the economic base of the North and Southeast of Brazil. In such regions, the advancement of world capitalism put those regional economies in contact with industrialized centers, which required rubber and coffee. The paths the respective economies placed them as the main sources of private fortune accumulation as well as taxes arrecadations. Belem and Sao Paulo became, at that time, fundamental poles of brazilian capitalism, being the main centers of those economies. However, when the source of rubber to industrialized economies began to shift to the tropical Asian rubber plantations, a serious crisis caused the Amazon region could not remain as one of the poles of brazilian capitalism, as had occurred between the years 1888 and 1917. The Southeast region, in contrast, remained significantly dynamic, confirming his post main center of the brazilian economy. It is known that foreign sources of capital were the main sources of financing of these economies. On the other hand, rubber and coffee production dynamics, from their internal accumulation patterns have given rise to domestic savings, which could be traded on a private credit market, boosting regional economies. Whereas various studies have indicated and analyzed the participation of foreign capital in these economies, this thesis deals a topic not yet addressed by the economic historiography: a comparative analysis of the role of domestic savings in financing activities and the economic and social life of Belem and Sao Paulo. In addressing the history of the indian rubber and coffee economies from the documental analysis of the characteristics of mortgage markets of its main squares, and institutional changes observed there, the aim was to bring the discussion new elements that help in understanding the different paths taken for those economies that made Sao Paulo emerged as the center and Belem as pole of a peripheral region of brazilian capitalism.